2012
DOI: 10.4067/s0717-95022012000100031
|View full text |Cite
|
Sign up to set email alerts
|

Influencia de la Extensibilidad Isquiosural en la Morfología Sagital del Raquis e Inclinación Pélvica en Deportistas

Abstract: RESUMEN:El objetivo de este estudio fue determinar la influencia de la extensibilidad isquiosural en la morfología sagital del raquis e inclinación pélvica en deportistas jóvenes. Métodos. Un total de 152 deportistas (media de edad: 16,22 ± 0,80 años) participaron voluntariamente en este estudio. La morfología sagital de las curvas torácica y lumbar, así como la inclinación pélvica, fueron evaluadas con un Spinal Mouse al realizar los test sit-and-reach, toe-touch y McRae & Wright. La extensibilidad isquiosura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…Recently, Sainz de Baranda et al [62] found a relative frequency of 84% hamstring tightness and 66.2% functional lumbar hyperkyphosis in 74 inline field hockey players. In contrast, hamstring tightness did not cause lumbar sagittal misalignments in rowers [94] and young athletes [95]. However, we should not forget that other factors such as weakness of the abdominal muscles [40,96]; and gluteal muscles [41], tightness of the hip flexors [37][38][39], and sagittal pelvic misalignment [36] also determine the alignment of the lumbar curve or not.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Sainz de Baranda et al [62] found a relative frequency of 84% hamstring tightness and 66.2% functional lumbar hyperkyphosis in 74 inline field hockey players. In contrast, hamstring tightness did not cause lumbar sagittal misalignments in rowers [94] and young athletes [95]. However, we should not forget that other factors such as weakness of the abdominal muscles [40,96]; and gluteal muscles [41], tightness of the hip flexors [37][38][39], and sagittal pelvic misalignment [36] also determine the alignment of the lumbar curve or not.…”
Section: Discussionmentioning
confidence: 99%
“…La mayor parte de estos estudios centran sus programas en la mejora de la flexibilidad isquiosural ya que su disminución puede afectar negativamente a la columna, provocando una retroversión de la pelvis (Latorre & Hernández, 2003) que puede afectar a la columna lumbar disminuyendo su curvatura, a la vez que se produce un incremento de la curvatura cifótica torácica como medida compensatoria (López-Miñarro, Muyor, Alacid, Rodríguez-García & López-Miñarro, 2012). El acortamiento de la musculatura isquiosural también puede dar lugar a otras patologías como lumbalgias (Feldman, Shrier, Rossignol & Abenhaim, 2001), espondilólisis (Standaert & Herring, 2000), espondilolistesis, enfermedad de Scheuermann, incluso hernias discales de la región lumbosacra (Kayser, Mahlfeld, Heyde, Grasshoff & Mellerowicz, 2006).…”
Section: Introductionunclassified